TASAWUF BĀ’ALAWĪ: SEJARAH DAN PENGARUHNYA - Kholili Hasib (DIRASAT: Jurnal Studi Islam dan Peradaban, 2018)
This research is a type of library research, trying to elucidate the role played by Ṭarīqah Bā’alawī in the Malay-Indonesian archipelago. Bā’alawī is the name attributed to ‘Alawī b. 'Ubaidillāh b. Aḥmad al-Muḥājir b. ‘Īsā b. Muḥammad b. ‘Alī al-‘Uraidi b. Ja'far al-Ṣādiq b. Muḥammad al-Bāqir b. ‘Alī Zainal Ābidīn b. Ḥusein b. Alī b. Abī Ṭālib. The research found that: (1) the teachings of Ṭarīqah Bā’alawī is a synthesis between imām al-Ghazālī and imām Abū al-Ḥasan al-Syādzilī; (2) Ṭarīqah Bā’alawī belongs to the school of Ahl al-Sussunnah wa al- Jamā'ah, and is said to maintain the Asy'arī creed and Syāfi‘ī jurisprudence